Peran Brand Image, Harga, dan Kualitas Produk pada Loyalitas Pelanggan Kosmetik Mother of Pearl - Septiawan, Dwiki; Octasylva, Annuridya Rosyidta Pratiwi; Vindiana, Afina Putri; Tampubolon, Edward S. (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to analyze the influence of brand image, price, and product quality on customer loyalty towards the Microblur Translucent Loose Powder product from the brand Mother of Pearl by Tasya Farasya. Data was collected through questionnaires distributed to customers using the product. Data analysis was performed using linear regression methods to test the proposed hypotheses. The results of the study indicate that brand image does not have a significant influence on customer loyalty, with a t-statistic value of 1.219, which is less than the critical value of 1.996, and a p-value of 0.223, which is greater than 0.050. Conversely, the variables of price and product quality show a significant influence on customer loyalty. The price has a t-statistic value of 2.392, which is greater than the critical value of 1.996, and a p-value of 0.017, which is less than 0.050. Product quality also shows a significant influence, with a t-statistic value of 2.005, which is greater than the critical value of 1.996, and a p-value of 0.045, which is less than 0.050. Based on these results, it can be concluded that in the customer loyalty model, the variables of price and product quality have a significant influence, while brand image does not have a significant influence on customer loyalty towards the Microblur Translucent Loose Powder product from the brand Mother of Pearl by Tasya Farasya.